Effectiveness of Conventional Rehabilitation Therapy on Postural Stability and Clinic in Stroke Patients with Hemiplegia - Ahmet Inanir; Sevil Okan; Behcet Filiz; Emre Kuyucu (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2013)
Objective: The aim of the present study was to determine the effectiviness of conventional rehabilitation in patients with stroke on static and dynamic balance as well as clinical assessment Methods: Twelve patients with stroke, 7 (58.33%) of them being male and 5 (41.66%) female, ranging from 51 to 75 in age who were treated in Physical Medicine and Rehabilitation clinic were involved in this study. The patients were treated with conventional rehabilitation. All individuals were evaluated using balance tests before (Group 1) and after (Group 2) the treatment. Balance level and postural control has been assessed through Berg Balance Scale (BBS), Trunk Control Test (TCT) and Biodex Stability System (BSS), motor level through BMIE, ambulation state through Functional Ambulatory Scale (FAS) and functional state in daily activities through Functional Independence Measure (FIM). The same tests were repeated while the patients were being discharged. Results: The mean age of the study population was 65,83±4,38 years, the average Body Mas Index (BMI) was 30,55±6,94. In the evaluations according to FIM, FAS, TCT and BBS differences between the mean of patients before and after the rehabilitation were significantly higher for the post-treatment (p=0.001, p=0.001, p=0.001 and p=0.001, respectively). In the evaluations according to Overall Stability Index (OSI), Antero-Posterior Stability Index (APSI) and Medio-Lateral Stability Index (MLSI) differences between the mean of patients before and after the rehabilitation were significantly higher for the pre-treatment (p=0.001, p=0.001 and p=0.001, respectively). Conclusion: It can be stated that this approach is effective and useful in restoring static and dynamic balance as well as in obtaining an effective improvement in the treatment of patients with stroke through conventional treatment. [Cukurova Med J 2013; 38(3.000): 446-455]